Collaboration between infection control and occupational health in three continents: a success story with international impact - Ndelu Lindiwe; Lavoie Marie-Claude; Breilh Jaime; Bryce Elizabeth A; Yassi Annalee; Lockhart Karen; Spiegel Jerry (BMC, 2011)
Abstract Globalization has been accompanied by the rapid spread of infectious diseases, and further strain on working conditions for health workers globally. Post-SARS, Canadian occupational health and infection control researchers got together to study how to better protect health workers, and found that training was indeed perceived as key to a positive safety culture. This led to developing information and communication technology (ICT) tools. The research conducted also showed the need for better workplace inspections, so a workplace audit tool was also developed to supplement worker questionnaires and the ICT. When invited to join Ecuadorean colleagues to promote occupational health and infection control, these tools were collectively adapted and improved, including face-to-face as well as on-line problem-based learning scenarios. The South African government then invited the team to work with local colleagues to improve occupational health and infection control, resulting in an improved web-based health information system to track incidents, exposures, and occupational injury and diseases. As the H1N1 pandemic struck, the online infection control course was adapted and translated into Spanish, as was a novel skill-building learning tool that permits health workers to practice selecting personal protective equipment. This tool was originally developed in collaboration with the countries from the Caribbean region and the Pan American Health Organization (PAHO). Research from these experiences led to strengthened focus on building capacity of health and safety committees, and new modules are thus being created, informed by that work. The products developed have been widely heralded as innovative and interactive, leading to their inclusion into "toolkits" used internationally. The tools used in Canada were substantially improved from the collaborative adaptation process for South and Central America and South Africa. This international collaboration between occupational health and infection control researchers led to the improvement of the research framework and development of tools, guidelines and information systems. Furthermore, the research and knowledge-transfer experience highlighted the value of partnership amongst Northern and Southern researchers in terms of sharing resources, experiences and knowledge.